Storage induced changes in sensory characteristics and viscosity of cocoa and whey protein enriched functional dairy drink - Gupta, H R (Indian Journal of Dairy Science, 2017)
The product developed in the present study was packaged in LDPE pouches stored at refrigeration temperature 4±1° C. The results of storage studies depicts that the product can be stored upto 18 days at 4±1° C without significantly affecting its sensory qualities. Overall acceptability scores decreased from initial 93.0 to 69.2 after 18 days of storage at 4±1° C for the drink enriched with whey protein; for the drink enriched with whey protein and cocoa, the scores decreased from 93.4 to 72.4. The consistency score of the product decreased from 27.5 to 19.5 for whey protein enhanced drink and from 27.7 to 20.6 in case of cocoa & whey protein enriched product after 18 days of storage at 4±1°C in LDPE pouch. The Color and appearance score decreased from 18.6 to 14.1 for the whey protein enriched drink and to 15.3 for the product enriched with cocoa & whey protein. The study clearly depicts that the sensory attributes viz. overall acceptability, flavor, taste, consistency and color &appearance scores between 15th and 18th day of storage of both the products differs significantly; indicating that the products are shelf stable upto 15th day when stored at 4±1º C.